Ginsenoside Re Attenuates High Glucose-Induced RF/6A Injury via Regulating PI3K/AKT Inhibited HIF-1α/VEGF Signaling Pathway - Xie, Weijie; Zhou, Ping; Qu, Muwen; Dai, Ziru; Zhang, Xuelian; Zhang, Chenyang; Dong, Xi; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2020)
Hyperglycaemia-induced retinal microvascular endothelial cell apoptosis is a critical and principle event in diabetic retinopathy (DR), which involves a series of complex processes such as mitochondrial dysfunction and oxidative stress. Ginsenoside Re (Re), a major component of ginseng, is considered to have various pharmacologic activities, including antioxidative, anti-inflammatory and anti-apoptotic properties. However, the effects and mechanisms of Re in diabetes-induced retinal angiogenesis and the potential mechanisms related to high glucose (HG) exposure remain unclear. This study aimed to investigate and evaluate the ability of Re to ameliorate HG-induced retinal endothelial RF/6A cell injury and the potential mechanisms related to the hypoxia inducible factor-1-alpha (HIF-1α) /VEGF signalling regulated by PI3K/AKT pathway. Our results showed that preincubation with Re exerted cytoprotective effects by reversing the HG-induced decrease in RF/6A cell viability, increase in apoptosis rate and downregulation of oxidative-related enzymes, thereby reducing the excess production of intracellular reactive oxygen species (ROS) and HG-induced RF/6A cell injury. In addition, Western blot analysis results showed ginsenoside Re significantly decreased HIF-1α expression in the cytoplasm but increased its expression in the nucleus, indicating that it reduced the translocation of HIF-1α from the cytoplasm to the nucleus, and downregulated vascular endothelial growth factor (VEGF) expression level. In addition, the phenomenon was related to the activation of the phosphoinositide 3-kinase (PI3K)/Akt pathway. Blocking the Akt pathway with LY294002, a PI3K inhibitor, the effects of Re on the regulation of apoptotic related proteins, VEGF and HIF-1α nuclear transcription was partially reversed. These findings suggested the exerting protective effects of ginsenoside Re were associated with regulating of PI3K/AKT and HIF-1α/ VEGF signalling pathway, which indicates that ginsenoside Re may ameliorates HG-induced retinal angiogenesis and suggests the potential for the development of Re as a therapeutic for diabetic retinopathy.